NGHỆ THUẬT TỰ SỰ TRONG TRUYỆN NGẮN “KHÔNG CÓ VUA” CỦA NGUYỄN HUY THIỆP - Võ Thị Bả (Tạp chí Giáo dục, 2023)
Narratology is a subject that that studies the narrative structure of story. The narrative theory focuses on studying the role of narrators in “engaging” in the text structure. Application of narrative theory into research works “No King” of Nguyen Huy Thiep helps students to understand the internal structure of the work and see the contribution of the writer as a creator.